Keeping the Lights On: The Impact of the COVID-19 Pandemic on Elective Total Joint Arthroplasty Utilization in the United States - Matthew W. Cole, MD; Lacee K. Collins, BS; Garrett H. Williams, MD; Olivia C. Lee, MD; William F. Sherman, MD, MBA (Arthroplasty Today, 2023)
Background: It was estimated that up to 30,000 primary total hip arthroplasty (THA) and total knee arthroplasty (TKA) procedures would be cancelled each week during the moratorium on elective surgeries in the United States. The purpose of this study was to analyze the impact of the COVID-19 pandemic on elective total joint arthroplasty utilization in the United States. Methods: A retrospective study was conducted using the PearlDiver database. Patients who underwent primary elective THAs and TKAs were identified and filtered by state and month from January through September of both 2019 and 2020. The volume of these procedures immediately following the moratorium on elective surgeries was compared to that of the same months the previous year. Results: For THA, overall, there was a 27.39% reduction in volume from 2019 to 2020 in March and an 88.94% reduction in April. For TKA, overall, there was a 31.28% reduction in volume in March and a 96.61% reduction in April. When the states were separated into 2 cohorts by the 2020 presidential election vote, there was a significantly larger decrease in THA and TKA volume observed in the 25 states and Washington DC that voted democrat than that in the 25 states that voted republican in both March (P < .05) and April (P < .05). Both THA (118.29%) and TKA (101.02%) volume returned to prepandemic levels by June. Conclusions: Overall, this study demonstrated that elective total joint arthroplasty utilization did reduce as anticipated following the CMS moratorium on elective surgeries but quickly returned to prepandemic levels by June. Level of Evidence: Level III.